Savings in a State with a Stationary Population: Comment - Arndt, H. W. (Quarterly Journal of Economics, 1948)
Journal Article Savings in a State with a Stationary Population: Comment Get access H. W. Arndt H. W. Arndt University of Sydney Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 62, Issue 4, August 1948, Pages 623–628, https://doi.org/10.2307/1881770 Published: 01 August 1948